2018
DOI: 10.1007/s12011-018-1317-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-analytical Factors Influence Accuracy of Urine Spot Iodine Assessment in Epidemiological Surveys

Abstract: Urinary iodine concentration (UIC) is commonly used to assess iodine status of subjects in epidemiological surveys. As pre-analytical factors are an important source of measurement error and studies about this phase are scarce, our objective was to assess the influence of urine sampling conditions on UIC, i.e., whether the child ate breakfast or not, urine void rank of the day, and time span between last meal and urine collection. A nationwide, two-stage, stratified, cross-sectional study including 1560 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This letter is regarding the recent publication of BPre-analytical factors influence accuracy of urine spot iodine assessment in epidemiological surveys^by Doggui et al (Biol Trace Elem Res 2018; https://doi.org/10.1007/s12011-018-1317-y) [1]. The findings by the authors are relevant and interesting.…”
mentioning
confidence: 94%
“…This letter is regarding the recent publication of BPre-analytical factors influence accuracy of urine spot iodine assessment in epidemiological surveys^by Doggui et al (Biol Trace Elem Res 2018; https://doi.org/10.1007/s12011-018-1317-y) [1]. The findings by the authors are relevant and interesting.…”
mentioning
confidence: 94%
“…Observational studies employing spot UIC for the assessment of nutritional iodine status reported conflicting findings on its relationship with obstetric complications and pregnancy outcomes [6][7][8] even if additional adjustment for urinary creatinine (UCr) was performed [9]. This could be due to UIC varying greatly with actual dietary iodine intake, season, and circadian rhythmicity [10], which could lead to the misclassification of iodine status and compromise the difference among different UIC groups. Accurate assessment of iodine nutrition is therefore essential, particularly during pregnancy [11].…”
Section: Introductionmentioning
confidence: 99%
“…These adjustments correct for between-subject variations in urine fluid volume and muscle mass [23][24][25]. As urinary concentrations of iodide reflect recent dietary intake of iodine-containing foods or beverages, other factors can also affect iodine status determination when using spot urine samples, such as skipping breakfast prior to morning urine sampling [26]. Although less convenient to collect, 24 h urine samples offer greater reproducibility and accuracy than spot urine samples and are the preferred method for assessing iodine status in epidemiological studies [27].…”
Section: Introductionmentioning
confidence: 99%